Engineering Graduates' Needs for Developing Their Employability Skills and Employers' Comments on Their Internships Performance - UMANG GARG, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The study looked at how learners in engineering should improve their employability skills and how it relates to how their internship performance was judged by the manager of the business. The research utilized an expressive research plan with 125 recent technical (engineering) learners from an Indian educational institute. The outcomes of the investigation showed that engineering learners received great rankings for their internship outcomes in terms of mindset, character, expertise, and abilities. They conducted an examination of employability abilities, along with cognitive skills and social skills, and found that the system thought talent has a very high development demand. They also thought about their existing work ethics and managerial skills, as well as their ability to read and write. A correlation test revealed an important negative correlation between the four facets of an apprenticeship assessment and the need for developing abilities in reading, math, time administration, and professional ethics, while a positive correlation was found between internship performance and the requirement for skill development in critical thinking and system thinking.